2019 IEEE World Haptics Conference (WHC) 2019
DOI: 10.1109/whc.2019.8816089
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact Cold Thermal Display by Controlling Low-temperature Air Flow Generated with Vortex Tube

Abstract: In recent years, thermal display has been studied intensively in order to represent a more realistic tactile quality of the object. Since human feels the temperature of the air without touching other objects, it is necessary to present thermal sensation in a non-contact manner. Studies on non-contact heat display have been explored; however, few studies have reported on a device that can display cold in a non-contact manner. In this study, we propose a non-contact cold thermal display using a low-temperature h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Blaga et al [6] analyzed the effect of thermal visual cues on users' grasping actions without inducing actual thermal stimulus. Xu et al [96] reported a non-contact cold thermal display using a vortex tube to generate ultra-low air temperature.…”
Section: Haptic Rendering Of Abnormal Sensationmentioning
confidence: 99%
“…Blaga et al [6] analyzed the effect of thermal visual cues on users' grasping actions without inducing actual thermal stimulus. Xu et al [96] reported a non-contact cold thermal display using a vortex tube to generate ultra-low air temperature.…”
Section: Haptic Rendering Of Abnormal Sensationmentioning
confidence: 99%
“…Han et al combined infrared lamp, mist, water drop and air conditioning [7]. Other non-contact-type methods are air transportations [20,22,31], humidity adjustment [9], vaporization [21],visuo-thermal interaction [18,19,27], and olfactory [2]. These non-contact-type methods do not require contacts to the devices that can result in reductions in the senses of immersion and presence.…”
Section: Related Workmentioning
confidence: 99%
“…For heating sensation, methods based on infrared lasers [Meyer et al 1976], thermal ladiation [Saga 2015], and high-intensity airborne ultrasound [Kamigaki et al 2020] have been proposed, which can display the heat sensations at a localized area remotely. For cooling sensation, methods based on atomized micro liquid mist [Arai et al 2012], low-temperature air-flow [Xu et al 2019] have been proposed, which can provide cooling sensation at localized areas; however, these methods require close-range (e.g., 5mm) from displays. For displaying the cooling sensation remotely, a method transporting cold air via straight narrow air-flow generated by the ultrasonic Bessel beam has been proposed [Nakajima et al 2018].…”
Section: Related Workmentioning
confidence: 99%